Macrofauna and biostratigraphy of the Rollrock Section, northern Ellesmere Island, Canadian Arctic Islands – a comprehensive high latitude archive of the Jurassic–Cretaceous transition - Schneider, S. (Simon); Kelly, S.R.A. (Simon R.A.); Mutterlose, J. (Jörg); Herrle, J.O. (Jens O.); Hülse, P. (Peter); Jolley, D.W. (David W.); Schroder-Adams, C. (Claudia); Lopez-Mir, B. (Berta) (Cretaceous Research, 2020)
The Rollrock Section in the Sverdrup Basin of Arctic Canada is one of the northernmost outcrops where the Jurassic-Cretaceous transition is accessible. The over 500 m thick sedimentary succession exposes the Oxfordian to Valanginian Ringnes and Deer Bay formations. Macrofauna from 15 discrete horizons includes ammonites, Buchia bivalves and belemnites. These fossils improve the biostratigraphy of the Tithonian and Berriasian in the Sverdrup Basin, provide correlation to the remainder of the Boreal Realm and set reliable calibration points. The occurrence of Buchia rugosa in the Ringnes Formation moves the upper formation boundary from the top of the Kimmeridgian into the lower Tithonian. Dorsoplanites maximus and D. sachsi document the middle Tithonian Dorsoplanites maximus Zone in Arctic Canada for the first time. The late Tithonian to early Berriasian Buchia terebratuloides is considered to be the best approximate indicator of the Jurassic-Cretaceous transition in the Rollrock Section. The middle early Berriasian Praetollia maynci and the late early Berriasian Borealites fedorovi tie the respective horizons to the successive Chetaites sibiricus and Hectoroceras kochi zones. Two species of the belemnite Arctoteuthis, collected from an interval with common glendonites, suggest a Valanginian age for the upper Deer Bay Formation. The dearth of Late Jurassic to earliest Cretaceous macrofossils in the Sverdrup Basin is inferred to be predominantly a function of diagenetic carbonate loss. Abundant dropstones and glendonites in the middle Tithonian to middle Valanginian interval suggest cold climatic conditions, and make the Rollrock Section a prime candidate for studying the Arctic environmental perturbations of this time.